Evaluation of surface expression of platelet markers and left ventricle ejection fraction in patients with coronary artery disease - Ghanbari, Fateme; Gordan, Hesamaddin; Gheydari, Mohammad Esmail; Karvandi, Mersedeh (Student Research in Translational Medicine, 2021)
Background and Aims: Surface expression of platelet markers enhanced during ischemic events and appear to play an important role in myocardial repair. Stromal cell-derived factor-1 (SDF-1) is one of these factors which its effects Mediated through CXCR4 and CXCR7 receptors. In our study we are going to determine the the surface expressions of platelet markers and the changes of left ventricle ejection fraction in patients with coronary artery disease. Materials and Methods: This descriptive cross-sectional study measured the superficial expression of platelet indices (SDF-1R, CXCR4, and CXCR7) and its association with the changes of the left ventricle ejection fraction in patients with coronary artery disease who have referred to Taleghani Hospital, Tehran in 2016-2018. Results: Among all patients referred to Taleghani Hospital with symptoms of coronary artery disease, 57 patient had inclusion criteria. this study demonstrated that mean SDF1 and CXCR4 level were respectively 1.1 and 2.3 which there were significant difference between those with severe EF reduction comparing to the rest of the groups (respectively P<0.002 & P<0.004 ). The mean CXCR7 value of all patients was 3.5 (SD= 0.27) and showed a significant difference in patients with severe (6) and low (4.7) ejection fraction reductions compared to those with moderate (2.5) and normal (2.8) ejection fraction reductions (P<0.009).